THE NORMAL FLORA OF THE ORAL MUCOSA IN LONG-TAILED MACAQUES AT THE MONKEY FOREST, UBUD - Agustina, Nadila; Soma, I Gede; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2025)
The long-tailed macaque is a monkey species found in various habitats, including primary and secondary forests. One population of long-tailed macaques in Bali can be found in the Monkey Forest, Ubud, Gianyar Regency. The normal oral flora of long-tailed macaques (Macaca fascicularis) plays a crucial role in their health and has potential impacts on the environment. Factors such as environment, diet, and age influence the health of long-tailed macaques living in the Monkey Forest, Ubud. This study aims to identify the bacterial present on the oral mucosa of long-tailed macaques (Macaca fascicularis) in the Monkey Forest, Ubud, and to assess their potential pathogenicity. The research design used in this study is observational with a cross-sectional study approach. Samples were collected using cotton swabs from the oral mucosa of long-tailed macaques. The bacterial identification was conducted using two agar media, namely Sheep Blood Agar (SBA) and MacConkey Agar (MCA), followed by biochemical tests. The data obtained in this study were analyzed descriptively. Based on the results of the conducted research, it can be concluded that three types of bacteria were found: Streptococcus sp. (53.3%), Fusobacterium sp. (40%), and Staphylococcus sp. (6.67%). Among the three bacteria identified, 46.67% have the potential to be pathogenic, namely Streptococcus sp. and Staphylococcus sp. Further studies are needed using molecular methods to specifically identify the bacterial species.